The Devil's bag man - Mansbach, Adam, 1976- (Harper Voyager, an imprint of HarperCollinsPublishers, 2015)
Locked in a Mexican jail for a crime he did not commit, Jess Galvan makes a devil's bargain to escape only to confront the hellish challenges of having his mind and body possessed by the five-hundred-year-old ghost of an Aztec priest.